Implementation Of Competitive Strategy: A Case Study On China Merchants Bank - Dong, Dai Yao (2007)
This study discusses China Merchants Bank\'s position, performances and the implementation of its strategies in the China\'s intense competitive environment. The background of the China banking industry and the undertaking reforms of its financial and banking industry are addresses. PEST environment analysis, SWOT analysis, Porter\'s five force analysis and several techniques have been employed in the case study of China Merchants Bank.